Correlation between cerebral small vessel disease and postural instability/gait difficulty subtype in Parkinson’s disease patients - Ge, Yingchao; Zhao, Wa; Xu, Xiaorong; Qiu, Wenchao; Liu, Peiting; Zhao, Minghui; Cheng, Yongqing; Xue, Shouru (Frontiers in Aging Neuroscience, 2025)
BackgroundPostural instability/gait difficulty (PIGD) subtype in Parkinson’s disease (PD) portends poorer prognosis and limited treatment response. While cerebral small vessel disease (CSVD) is implicated in motor impairment, its specific association with PIGD remains underexplored. This study aims to investigate the correlation between the severity of CSVD and PIGD subtype in PD patients.MethodsThis cross-sectional study enrolled 161 PD patients (mean age 71.14 ± 7.04 years). Motor subtyping [postural instability and gait difficulty (PIGD)/tremor-dominant (TD)/intermediate type (IT)] used MDS-UPDRS-derived ratios. CSVD burden was quantified via two validated MRI-based scores: the total CSVD burden score (range 0–4) and modified CSVD burden score (range 0–6). Multivariate logistic regression analysis, which adjusted for age, gender, disease duration, and vascular risk factors, was used to explore the correlation between CSVD burden and PIGD.ResultsThe prevalence of PIGD was 49.07% (n = 79). PIGD patients exhibited a significantly higher CSVD burden than the TD and IT groups (total score: 1.84 ± 0.72 vs. 1.4 ± 0.59 vs.1.15 ± 0.49; modified score: 2.55 ± 1.20 vs. 1.85 ± 0.7 vs. 1.75 ± 0.91, both p < 0.001). After full adjustment, each 1-point increase in total CSVD burden score associated with 7.16-fold higher PIGD odds (aOR = 7.16, 95%CI = 1.64–30.82, p = 0.009), and each 1-point increase in modified CSVD burden score associated with 6.03-fold higher PIGD odds (aOR = 6.03, 95%CI = 3.06–11.90, p < 0.001).ConclusionGlobal CSVD burden was independently associated with the occurrence of PIGD in PD. CSVD assessment may help identify PD patients at the highest risk for axial motor disability, highlighting the convergence of vascular and neurodegenerative pathologies.